Book Review: M. V. Nadkarni, N. Sivanna and Lavanya Suresh, Decentralised Democracy in India: Gandhi's Vision and Reality. (December 2018) - Venkatesu, E.
M. V. Nadkarni, N. Sivanna and Lavanya Suresh, Decentralised Democracy in India: Gandhi's Vision and Reality . New Delhi: Routledge. 2018. 420 pages. ₹1, 295.